Revisiting the Nexus between Climate Change and Unemployment in South Africa (Acta Universitatis Danubius. Œconomica, 2024)
Emancipating policy coherence and achieve a sustainable future, it is essential to identify thelinkages between the 17 Sustainable Development Goals (SDGs) put out by the UN. Sequel to this, thestudy revisits the nexus between climate change and unemployment in South Africa. The studyemployed time series data span through 1986-2021. The ARDL econometric techniques is used toevaluates the nexus amid the variables. Given that the long-term coefficient of climate change (Tpr) ispositive and statistically significant at the 5% level, the long-run result support the expected sign thatclimate change has a positive impact on unemployment in South Africa. The government of SouthAfrica need thus concentrate more on lowering the country’s inflation rate and strengthening the localcurrency relative to the US dollar. In the meantime, the shortage of jobs in South Africa will worsendue to the rise in unemployment brought on by the rising temperatures. Here, the government shouldincrease funding at the federal level for a number of industries, including forestry, tourism, agriculture,and fisheries, that are heavily reliant on climate change.